1995
DOI: 10.1002/j.1460-2075.1995.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid in the SH3 domain of Hck determines its high affinity and specificity in binding to HIV-1 Nef protein.

Abstract: We have examined the differential binding of Hck and Fyn to HIV‐1 Nef to elucidate the structural basis of SH3 binding affinity and specificity. Full‐length Nef bound to Hck SH3 with the highest affinity reported for an SH3‐mediated interaction (KD 250 nM). In contrast to Hck, affinity of the highly homologous Fyn SH3 for Nef was too weak (KD > 20 microM) to be accurately determined. We show that this distinct specificity lies in a variable loop, the ‘RT loop’, positioned close to conserved SH3 residues implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
256
2
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(273 citation statements)
references
References 40 publications
(66 reference statements)
14
256
2
1
Order By: Relevance
“…For a`consolidated ligand', a peptide which binds simultaneously to the SH2 and SH3 domains of the Abl kinase protein, an a nity of approximately 250 nM was measured . The a nity of the HIV Nef protein to the HckSH3 domain, determined by surface plasmon resonance (SPR) and isothermal titration calorimetry (ITC), is also similar (Lee et al, 1995) but the corresponding Nef-peptide bound with a K d of 91 mM (measured by Trp-¯uorescence).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For a`consolidated ligand', a peptide which binds simultaneously to the SH2 and SH3 domains of the Abl kinase protein, an a nity of approximately 250 nM was measured . The a nity of the HIV Nef protein to the HckSH3 domain, determined by surface plasmon resonance (SPR) and isothermal titration calorimetry (ITC), is also similar (Lee et al, 1995) but the corresponding Nef-peptide bound with a K d of 91 mM (measured by Trp-¯uorescence).…”
mentioning
confidence: 87%
“…C3G, a guanine-nucleotide exchange factor for the GTPases Rap 1 A and B (Gotoh et al, 1995), contains four potential CrkSH3 binding motifs (CB1 to CB4) clustered in the central region of the protein (Knudsen et al, 1994;Tanaka et al, 1994). A 10-amino acid peptide corresponding to the CB1-motif was found to bind the CrkSH3(1) domain with a K d of 1.9 mM , a remarkably high a nity when compared to other SH3-interacting peptides of this length measured with tryptophan¯uorescence (Lee et al, 1995). A conserved lysine residue present in all C3G-CB motifs (consensus P-P-x-L-P-x-K) contributes greatly to the peptide and protein binding speci®city of the CrkSH3(1) domain.…”
Section: Introductionmentioning
confidence: 99%
“…In macrophages, three kinases of the Src family are expressed: Hck, Lck/Yes-related novel protein, and Gardner-Rasheed feline sarcoma (51). Interaction of Nef with Hck has been described as the highest affinity among the Src family kinases (21). Nef triggers Hck activation, whereas it has no effect on Lck/Yes-related novel protein activity and Gardner-Rasheed feline sarcoma is not a target of Nef (52).…”
Section: Nef Induces Macrophage Fusion In An Hck-dependent Mannermentioning
confidence: 99%
“…HIV-1 Nef interacts with the Src homology 3 (SH3) domains of Src PTKs through a proline-rich (P72xxP75) motif in its core domain, and substitution of a single amino acid in the Nef PxxP motif was sufficient to protect HIV-1 transgenic mice from the development of AIDS-like disease (19,20). Binding of Nef to SH3 domains can inhibit the T cell-specific Lck kinase activity or activates the phagocyte-specific kinase hematopoietic cell kinase (Hck) (21). The binding affinity between Nef and Hck is the highest among the SH3-mediated interactions (22,23); however, very little is known about the functional consequences of Hck activation by Nef in macrophages.…”
mentioning
confidence: 99%
“…Using filterbinding assays and plasmon resonance it was shown that the Nef proline motif bound to the SH3 domain of Hck with high affinity (K D 250 nM for intact Nef but 300-fold weaker for the , p97, p75, p57, p55, p32, p28, p26 p70, p60, p56, p44, p36, p32, p30, p28, p27 Sawai et al (1994) Harris & Neil (1994) Rossi et al (1996) Harris ( Benichou et al (1994) Harris (1995) isolated PxxP motif) Lee et al, 1995). An additional PxxP motif at amino acids 147-150 was also implicated in the interaction, possibly explaining the decreased affinity of the isolated PxxP motif.…”
Section: Clues To the Biochemistry Of Nef Function From The Identificmentioning
confidence: 99%